Asesmen Kualitas RTH Publik Menggunakan Indeks Vegetasi di Taman Hutan Raya Ir. H. Djuanda Kota Bandung - Muhammad Alwan Faris Fadlirullah Raden, Sutadiwangsa; Adytia Heru Nugraha; Ammar Muhammad Nabil; Yulia Asyiawati (Universitas Pelita Harapan, 2026)
Urban forest ecosystems are increasingly subject to significant anthropogenic pressures; however, the resulting ecological responses often exhibit a delayed manifestation. The Ir. H. Djuanda Forest Park (Tahura) serves as a vital urban conservation area in Bandung, Indonesia, which has experienced a massive surge in tourist volume. This study aims to analyze the